Prevention and correction of behavioral disorders in rats with metabolic syndrome using a complex phytoadaptogen - Zh. V. Dzampaeva; F. S. Datieva; E. A. Takoeva; M. I. Nartikoeva (Acta Biomedica Scientifica, 2024)
The aim of the study. To assess the possibility of correction and prevention of behavioral disorders in rats with metabolic syndrome using a complex phytoadaptogen (CPA).Material and methods. The experiment was carried out on 30 male Wistar rats randomized into 3 groups: group 1 – control; group 2 – metabolic syndrome (MS); group 3 – treatment of metabolic syndrome using CPA. In groups 2 and 3, animals were on a high-carbohydrate and high-fat diet for 16 weeks. Group 3 received CPA for 14 days in drinking water after 16 weeks of a diet. CPA consists of official tinctures of Glycyrrhiza glabra, Rhodiola rosea, Acantopanax senticosus at a ratio of 1:2:1. Behavior was analyzed through the “open field” test using Realtimer software (Open Science, Russia). Data were analyzed using GraphPad Prism 8.03 software (GraphPad, USA).Results. The experiment proved that metabolic syndrome is accompanied by increased anxiety (decreased horizontal (p  =  0.017) and  vertical (p  =  0.017) motor activity) and fear (increased periods of immobility (p = 0.011)) in the open field. When corrected with a complex phytoadaptogen, the time spent in the open and closed arms of the maze did not differ statistically significantly from the values of similar control indicators.Conclusion. Based on the data obtained in the group 3 (no statistically significant differences with control) – decreased manifestations of fear and anxiety (increased orientation and research activity) – we can talk about the effectiveness of complex phytoadaptogens as an anxiolytic. The mechanisms underlying this result remain to be explored, emphasizing the role of the autonomic nervous system, leptin and ghrelin in behavior and the influence of complex phytoadaptogens on them.